Factors Influencing Consumer Satisfaction with Bojonegoro's Typical Souvenir Product "Ledre Asli" - Khoirot, Nur Lum’atul; Irianto, Heru; Riptanti, Erlyna Wida (International Journal of Education, Information Technology, and Others, 2024)
In the era of globalization filled with intense business competition, corporate organizations or businesses have a strong drive to survive. Factors influencing consumer satisfaction, including assessments of product quality, become crucial in efforts to maintain consumer loyalty. An example is "Ledre Asli," a typical Bojonegoro culinary product from micro, small, and medium enterprises (MSMEs) facing the challenge of insufficient promotion. This study aims to identify factors influencing consumer satisfaction with the product, with emphasis on the relationship between consumer satisfaction and repeat purchase intention. The research method employed is associative, aiming to reveal the relationship between two relevant variables in this context.